DELHI NCR CORPORATE LIBRARY MARKETING STRATEGIES - Kumari Anuradha (International Journal of Multidisciplinary Research and Studies, 2021)
The parent organizations of libraries demand a Return on Investment (ROI) for every amount of money that is spent on libraries. According to Mercado3 (1998), "the effects of globalization and liberalization are gradually transforming this scenario totally." While it is expected of librarians to provide the quickest, most up-to-date, and most expensive gear and software available in order to make the information marketplace accessible, it is also expected that librarians will downsize, save money, and streamline their operations. The function of a librarian today is very different from what it was in the past. Now, not only do they have to run the library, but they also have to make sure that every user has access to the library's materials, which may be found in the library.